2008
DOI: 10.1152/physiolgenomics.00142.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term growth hormone treatment on liver and muscle transcriptomes in rainbow trout (Oncorhynchus mykiss)

Abstract: Gahr SA, Vallejo RL, Weber GM, Shepherd BS, Silverstein JT, Rexroad CE 3rd. Effects of short-term growth hormone treatment on liver and muscle transcriptomes in rainbow trout (Oncorhynchus mykiss).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 64 publications
7
32
0
Order By: Relevance
“…These findings are consistent with previous data showing alterations in many processes including nutritional requirements, energetics, muscle fibre structure, and cartilage deposition in transgenic fish (25,(30)(31)(32)(33)(34)(35). Complex effects on metabolism and GH receptor expression have also been observed in liver and muscle in rainbow trout treated with GH protein (36).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous data showing alterations in many processes including nutritional requirements, energetics, muscle fibre structure, and cartilage deposition in transgenic fish (25,(30)(31)(32)(33)(34)(35). Complex effects on metabolism and GH receptor expression have also been observed in liver and muscle in rainbow trout treated with GH protein (36).…”
Section: Discussionsupporting
confidence: 93%
“…For IGF-I this is consistent with previous reports in fish including our own transgenic tilapia (Eppler et al 2007a) that GH treatment stimulates liver IGF-I gene expression. For IGF-II expression, no GH effect was found in gilthead seabream (Duguay et al 1996) but, in accordance with our results, GH increased IGF-II mRNA levels in rainbow trout, common carp and Japanese eel (Shamblott et al 1995;Vong et al 2003;Moriyama et al 2008), and in rainbow trout and redbanded seabream, similar to our findings in tilapia, more pronouncedly than IGF-I mRNA (Gahr et al 2008;Ponce et al 2008). IGF-II mRNA in muscle was similarly increased in the GH-overexpressing fish as found previously for IGF-I mRNA (Eppler et al 2007a) which suggests that expression of both IGFs in muscle is under control by GH.…”
Section: Discussionsupporting
confidence: 91%
“…Surprisingly, this microarray analysis detected only a small set of genes coding for hepatic enzymes, most notably fatty acid desaturase and prostaglandin D synthase. Similarly, a more recent study evaluating the transcriptional response of the rainbow trout liver to a short-term (3 days) treatment with GH and using the same GRASP microarray also reported changes in a small set of genes, very few of those corresponding to hepatic enzymes (Gahr et al 2008). In this study, the two major functional categories that responded to administration of GH were genes involved in metabolism and immune response.…”
Section: Transcriptional Changes In the Liver In Relation To Growth Asupporting
confidence: 62%
“…However, until very recently, global transcriptional changes in muscle of GH transgenic salmon had not been evaluated using high-throughput approaches. A recent study has reported on the effects of exogenous bovine GH administration on the rainbow trout muscle transcriptome using the GRASP 16 K cDNA microarray (Gahr et al 2008). In this study, GH was injected in fish from two different rainbow trout families, selected for low-and high-growth rates, and different sets of genes up-and down-regulated were identified in white muscle mediating cellular processes such as cell cycle, immune response, metabolism or protein degradation.…”
Section: Transcriptomic Changes In Skeletal Muscle Related To Muscle mentioning
confidence: 99%